Gibbs energies of protonation and complexation of platinum and vanadate metal ions with naringenin and phenolic acids: Theoretical calculations associated with experimental values. (September 2016) - Fazary, Ahmed E.; Alshihri, Ayed S.; Alfaifi, Mohammad Y.; Saleh, Kamel A.; Elbehairi, Serag Eldin I.; Fawy, Khaled F.; Abd-Rabboh, Hisham S.M.
Graphical abstract: Highlights: The experimental thermodynamic equilibrium and stability constants of vanadium and platinum complexes involving naringin, ferulic acid, p-coumaric acid, caffeic acid, vanillic acid, sinapic acid, and gallic acid were determined. The theoretical calculations of the free energy changes associated with the ligand protonation, and metal ion–ligand complex formation equilibria using density function theory calculations, providing a complete picture of the microscopic equilibria of the studied complex systems. Abstract: The Experimental thermodynamic equilibrium ( p Ka values) and stability (log  β ) constants of vanadium and platinum binary and mixed ligand complexes involving naringenin, ferulic acid, p-coumaric acid, caffeic acid, vanillic acid, sinapic acid, and gallic acid were determined at 310.15 K in 0.16 mol·dm −3 KCl aqueous solutions using pH-potentiometric technique and by means of two estimation models (HYPERQUAD 2008 and Bjerrum–Calvin). The theoretical calculations of overall protonation and stability constants of the metal complex species in solution were predicted as the free energy change associated with the ligand protonation, and metal ion–ligand complex formation equilibria (species solvation/de-solvation) using ab initio and density function theory (DFT) calculations. The usage of the experimental potentiometry technique and theoretical predictions provides a complete picture of the microscopic equilibria of the studied systems (vanadium/platinum–naringenin–phenolic acid). Specifically, this theoretically DFT predications would be useful to determine the most real protonation constants of the studied bioligands in which the binding sites changes due to the ligand protonation/deprotonation equilibria. Also, the complexing capacities of vanadium and platinum towards naringenin, ferulic acid, p-coumaric acid, caffeic acid, vanillic acid, sinapic acid, and gallic acid in solutions were evaluated and discussed. From the determined experimental stability constants of different metal complex species, the concentration distribution diagrams of the various metal ion complex species in solution was estimated using HySS 2009 software.